Neonatal infection in premature infants and use of human immunoglobulin. Issue 12 (December 1987) - Conway, S P; Gillies, D R; Docherty, A
Abstract : In an open study 120 consecutively admitted premature babies of 32 weeks' gestation or less, were randomised to receive weekly intramuscular injections of human normal immunoglobulin (50 mg/kg). There was no significant difference between the number of babies in the treated and untreated groups who had at least one episode of infection, but the total number of infective episodes was substantially less in the treated group (n = 22) compared with 40 in the non-treated group. Three babies died from overwhelming infection and three babies developed necrotising enterocolitis, all in the group that had not been treated. Serum IgG concentrations were significantly higher in the treated group by the age of 2 weeks but remained consistently below those of full term babies of similar postnatal age. Administration of human immunoglobulin may decrease the severity of infection in premature babies, but alternative regimens may be more successful.